Unveiling the Potential of AI: Shaping the Future of Scientific Research - Ettaouass , Mohammed (Revue Internationale du Chercheur, 2025)
Integrating Artificial Intelligence (AI) into scientific research is a revolutionary change that is transforming approaches and speeding up discoveries. This abstract explores the influence of AI on the scientific field, emphasizing its ability to help researchers analyze large datasets, identify trends, and produce innovative findings. The study focuses on how university students use AI tools for research, evaluating their effectiveness and assessing their understanding of AI mechanisms and implications. The study adopts a mixed-methods approach, incorporating questionnaires and focus group discussions, to investigate the many roles of AI in academic environments, with the goal of clarifying how students use AI and its impact on research. The assessment examines students' understanding of AI, including its use in driving innovative breakthroughs and the ethical issues involved. This paper supports the intentional incorporation of AI into scientific investigation, highlighting AI's significant potential to drive innovation. It aims to promote responsible AI usage that upholds academic integrity. It also suggests that integrating AI into research can create exceptional potential for progress, leading to a future where human intelligence and artificial intelligence work together to discover new possibilities.